Pengaruh Fasilitas Dan Kualitas Layanan Terhadap Kepuasan Pelanggan Pada SPBU Pertamina Marifat Di Kradenan Banyuwangi - Muhammad Aghistni Maulana Salsabil; Muhammad Ridwan Basalamah; Rahmawati Rahmawati (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This research was conducted at Pertamina Marifat gas station in Kradenan Banyuwangi. The type of research used is explanatory research with a quantitative approach. The purpose of this study was to determine the effect of facilities and service quality on customer satisfaction. The independent variables used are facilities and service quality, while the dependent variable is customer satisfaction. The sample used in this study were 65 respondents who were consumers of Pertamina Marifat gas stations in Kradenan Banyuwangi. Data collection techniques using a questionnaire. The analytical method used is instrument test, path analysis, f test and t test of determination using IBM SPSS computer software for data processing. The results of this study indicate that the facilities and service quality have a direct effect on customer satisfaction. Keywords: Facilities, Service Quality, Customer Decision..